Directed organization of gold nanoclusters on silver nanowires: a step forward in heterostructure assembly - Sharma, J.; Vivek, J. P.; Vijayamohanan, K. P.; Singh, P.; Dharmadhikari, C. V. (Applied Physics Letters, 2006)
We investigate the directed assembly of tridecylamine protected gold nanoclusters of 4-5 nm size on functionalized silver nanowires of 55-60 nm diameter and the electron transfer behavior of this integrated structure using transmission electron microscopy, non-contact atomic force microscopy, and scanning tunneling microscopy/spectroscopy. Linear I-V for bare silver nanowire suggests metallic behavior but high tunnel resistance indicates presence of insulating layer on the surface. Identical I-Vs obtained for isolated gold nanoparticle and heterostructure suggests that electron transport across nanowires in the latter is governed by gold nanoparticles in contrast to expected ballistic or diffusive transport along their length.(c) 2006 American Institute of Physics.

Scanning tunneling microscopy/spectroscopy on Au nanoparticles assembled using lauryl amine (LAM) and octadecane thiol (ODT) - Datar, Suwarna; Chaudhary, Minakshi V.; Sastry, Murali; Dharmadhikari, C. V. (Applied Surface Science, 2007)
In this report, we demonstrate scanning tunneling microscopy and spectroscopy on thin filins of lauryl amine (LAM) and octadecane thiol (ODT) protected gold nanoparticles. We show that the zero current in the I-V curves (measure of Coulomb blockade (CB) of the nanoparticles) depends on the properties of the spacer molecule. In both the cases the gap voltage and the tunneling current at which the images are obtained are quite different which is further confirmed from the fitting performed based on the orthodox theory. The values for the capacitance and charging energy obtained from the fitting for ODT capped particles are comparable to the values obtained using spherical capacitor model. In contrast, values of these parameters were found to differ for LAM capped nanoparticles. While imaging, ODT capped nanoparticles were observed to drag along the scan direction leading to ordering of particles. Images of LAM capped gold nanoparticles show local ordering in self-assembly of particles although no evidence of large scale ordering in spatial Fourier transform was seen. These observations suggest that nanoparticles with larger CB would be intaged nonevasively in contrast to small CB systems for which tip induced effects will be dominant. In both the systems the current was found to rise faster than theoretical curves based on the orthodox theory suggesting that mechanism of charge transfer in this case may involve field emission rather than tunneling through a rectangular barrier. An attempt has been made to explain charge transfer based on Fowler-Nordheim (F-N) plots of the I-V curves. (c) 2006 Elsevier B.V All rights reserved.
Keywords: Nanostructures; scanning tunneling microscopy (STM)

New approach towards imaging lambda-DNA using scanning tunneling microscopy/spectroscopy (STM/STS) - Dey, Shirshendu; Pethkar, Sushama; Adyanthaya, Suguna D.; Sastry, Murali; Dharmadhikari, C. V. (Bulletin of Materials Science, 2008)
A new methodology to anchor A-DNA to silanized n-Si(111) surface using Langmuir Blodget trough was developed. The n-Si (111) was silanized by treating it with low molecular weight octyltrichlorosilane in toluene. Scanning tunneling microscopy (STM) image of lambda-DNA on octyltrichlorosilane deposited Si substrate shows areas exhibiting arrayed structures of 700 nm length and 40 nm spacing. Scanning tunneling spectroscopy (STS) at different stages depict a broad distribution of defect states in the bandgap region of n-Si(111) which presumably facilitates tunneling through otherwise insulating DNA layer.
National Review and Coordination Meeting on Nanoscience and Nanotechnology, Hyderabad, INDIA, 2007
Keywords: DNA; Langmuir Blodget technique; Scanning tunneling microscopy; silanization

Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Charge storage and electron transport properties of gold nanoparticles decorating a urethane-methacrylate comb polymer network - Patil, Sumati; Datar, Suwarna; Rekha, N.; Asha, S. K.; Dharmadhikari, C. V. (Nanoscale, 2013)
We propose enhanced charge storage capacity of nanoparticles based polymer films. A flat band voltage window varying from 5-7 V is obtained leading to a trapped charge density of the order of 10(13) cm(-2). These results vary for two distinct morphologies obtained due to decoration of a urethane-methacrylate comb polymer (UMCP) network by gold nanoparticles (AuNPs). Films have been further investigated for morphology, optical, charge storage, and electron transport properties using techniques like scanning electron microscopy (SEM), atomic force microscopy (AFM), absorption spectroscopy (UV-Vis), scanning tunneling microscopy/spectroscopy (STM/STS) and capacitance versus voltage (C-V) measurements. SEM and AFM confirm either the deposition of AuNPs inside the UMCP network or the formation of ring like structures depending on the deposition sequence. STS measurements performed on both films are compared with bare UMCP and AuNPs films. Current versus voltage (I-V) characteristics so obtained are discussed in the light of electron transport mechanisms in such materials.

Investigation of disorder in mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon - Patil, Sumati; Kolekar, Sadhu; Kumar, Arvind; Alegaonkar, Prashant; Datar, Suwarna; Dharmadhikari, C. V. (Journal of Nanoscience and Nanotechnology, 2018)
Disorder in a mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon (GNC) lattice has been extensively studied for its electronic and field emission properties. Morphological investigations are performed using scanning electron microscopy (SEM) which depicts microstructures comprising of atomically flat terraces (c-planes) with an abundance of edges (ab planes which are orthogonal to c-planes). Scanning tunneling microscopy (STM) is used to observe the atomic structure of basal planes whereas field emission microscopy (FEM) is found to be suitable for resolving nanotopography of edges. STM images revealed the hexagonal and non-hexagonal atomic arrangements in addition to a variety of defect structures. Scanning tunneling spectroscopy is carried out to study the effect of this short-range disorder on the local density of states. Current versus voltage (I-V) characteristics have been recorded at different defect sites and are compared with respect to the extent of the defect. As sharp edges of GNC are expected to be excellent field emitters, because of low work function and high electric field, enhancement in current is observed particularly when applied electric field is along basal planes. Therefore, it is worthwhile to investigate field emission from these samples. The FEM images show a cluster of bright spots at low voltages which later transformed into an array resembling ledges of ab-planes with increasing voltage. Reproducible I-V curves yield linear Fowler-Nordheim plots supporting field emission as the dominant mechanism of electron emission. Turn on field for 10 mu A current is estimated to be similar to 3 V/mu m.
Keywords: Field emission microscopy; Graphene-Like Nanocarbon; Scanning tunneling microscopy; Scanning Tunneling Spectroscopy